2017
DOI: 10.1002/ir.20191
|View full text |Cite
|
Sign up to set email alerts
|

Student Veterans in Higher Education: A Conversation Six Decades in the Making

Abstract: This chapter provides a historical overview of the relationship between the military and higher education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Furthermore, the failure of institutions to promote progress of veterans toward graduation meant the loss of federal and state funds (Dillard & Yu, 2016;Fouad & Ghosh, 2018;Geiger, 2015;Vick & Fontanella, 2017). Dillard and Yu (2016) and Hammond (2017) reported that veterans using the GI Bill were U.S. citizens, males, and fulltime students. Today's veterans are more diverse.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the failure of institutions to promote progress of veterans toward graduation meant the loss of federal and state funds (Dillard & Yu, 2016;Fouad & Ghosh, 2018;Geiger, 2015;Vick & Fontanella, 2017). Dillard and Yu (2016) and Hammond (2017) reported that veterans using the GI Bill were U.S. citizens, males, and fulltime students. Today's veterans are more diverse.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, they found that about 48% of activeduty service members and 47% of reservists were ethnic minorities. Hammond (2017) identified that an increased number of service members survived their war injuries and returned home. Such injuries caused significant trauma to their bodies and/or to their mental health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The passage of the SRA changed the relationship between the military and higher education from one of training to re-training. The end of World War II saw the discharge of millions of service members, and in response, Congress passed the SRA to mitigate the potential negative impact such an influx could have on the economy (Hammond, 2017). The SRA provided veterans with financial benefits, including unemployment support, loans for housing and businesses, and access to postsecondary education (Rumann & Hamrick, 2009).…”
Section: History Of the Relationship Of Higher Education And The Armementioning
confidence: 99%
“…These students have changed significantly since the original G.I. Bill of 1944 (Eagan, McBain, & Jones, 2017;Hammond, 2017). After the Post-9/11 G.I.…”
Section: Newly Assessed Emerging Aspects Of Student Identitymentioning
confidence: 99%
“…Bill had colleges and universities across the country experienced such a significant increase in student veteran enrollment. Combat experience and the effects of serving in the military during active wartime can impact students' emotional well-being and their ability to adjust to and succeed in college (Hammond, 2017).…”
Section: Newly Assessed Emerging Aspects Of Student Identitymentioning
confidence: 99%